The flexible-transparent p-n junction film device of N-doped Cu2O/SnO2 orderly nanowire arrays towards highly photovoltaic conversion and stability - Pan, Jiaqi; Li, Shi; Liu, Yanyan; Ou, Wei; Li, Hongli; Zhao, Weijie; Wang, Jingjing; Song, Changsheng; Zheng, Yingying; Li, Chaorong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •The N-doping could regulate the band gap to increase the transmittance.•The N-doping could improve the charge carriers transport and lifetime.•The orderly SnO2 nano-arrays could increase the flexible stability. The flexible-transparent N-doped Cu2O/SnO2 p-n junction film device is prepared via a simple hybrid hydrothermal-sputtering method. There, the SnO2 nanowire arrays are induced by the pre-sputtered seeds and grown on the flexible PEN substrate via hydrothermal method, and subsequently the N-doped Cu2O film is deposited via radio-frequency sputtering. As revealed, the flexible-transparent device exhibits highly transmittance of about ~85% in visible light, obvious photovoltaic conversion enhancement of about ~1500 folds than the undoped device, and decent flexible stability of about ~91% during the 1000 times bending, which is regarded as a decent flexible-transparent photovoltaic device and can be mainly ascribed to the N-doping can regulate the band gap to increase the transmittance, reduce the crystal defect to improve the charge carriers, including the interface transport rate and lifetime, the orderly SnO2 nano-arrays can release the interfacial stress to increase the flexible stability.